Ćwiczenia kształtujące w profilaktyce wad postawy u dzieci w wieku wczesnoszkolnym - Bąkowicz, M.; Бакович М. (Східноєвропейський національний університет ім. Лесі Українки, 2012)
One of the most important tasks of physical education ina secondary school is posture disorders prevention among junior pupils. In the process of an experiment different gymnastic exercises were done, they were chosen individually for every pupils according to the condidtion of his posture and were done systematically during lessons of physical education. Conducted reseach has shown their effectiveness. Body posture among children from the experimental group was much better than control group. Одним із важливих завдань фізичного виховання дітей загальноосвітньої школи є профілактика порушень постави учнів початкових класів. У процесі експерименту застосовано різноманітні гімнастичні вправи, які підбирали індивідуально для кожного учня залежно від стану його постави та які виконувалися систематично під час уроків фізичної культури. Проведене дослідження показало їх ефективність. Постава тіла в дітей експери¬ментальної групи була значно кращою, ніж контрольної.
Shaping Exercises as Means of Prevention of Postural Disorders Among Junior Pupils
Keywords: education; future employers; postural disorders; health; учні початкових класів; постава; профілактика